Histone modifications related to chromosome silencing and elimination during male meiosis in Bengalese finch - del Priore, Lucía (2014)
We report here that a germline-restricted chromosome (GRC) is regularly present in males and females of the Bengalese finch (Lonchura domestica). While the GRC is euchromatic in oocytes, in spermatocytes this chromosome is cytologically seen as entirely heterochromatic and presumably inactive. The GRC is observed in the cytoplasm of secondary spermatocytes, indicating that its elimination from the nucleus occurs during the first meiotic division. By immunofluorescence on microspreads, we investigated the presence of histone H3 modifications throughout male meiosis, as well as in postmeiotic stages. We found that the GRC is highly enriched in di- and trimethylated histone H3 at lysine 9 during prophase I, in agreement with the presumed inactive state of this chromosome. At metaphase I, dimethylated histone H3 is no longer detectable on the GRC and its chromatin is more faintly stained with DAPI. The condensed GRC is underphosphorylated at serine 10 compared to the regular chromosomes during metaphase I, being phosphorylated later at this site after the first meiotic division. From these results, we proposed that trimethylation of histone H3 at lysine 9 on the GRC chromatin increases during metaphase I. This hypermethylated state at lysine 9 may preclude the phosphorylation of the adjacent serine 10 residue, providing an example of cross-talk of histone H3 modifications as described in experimental systems. The differential underphosphorylation of the GRC chromatin before elimination is interpreted as a cytologically detectable byproduct of deficient activity of Aurora B kinase, which is responsible for the phosphorylation of H3 at serine 10 during mitosis and meiosis.